SKRINING THALASEMIA-BETA MINOR PADA MAHASISWA FAKULTAS KEDOKTERAN - Fransiska Anggreni Sihotang; Loly Rotua Dharmanita Siagian; Novia Fransiska Ngo; Lily Pertiwi Kalalo (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2019)
Thalassemia is a group of congenital hemoglobinopathy characterized by deficiency or absence of one (or more) of the globin chains that constitute hemoglobin. Thalassemia major is inherited through autosomal recessive pattern by marriage between carriers of the thalassemia gene known as thalassemia minor. Beta-thalassemia is the most common type of thalassemia. It is estimated that 10% of Indonesia's population carries the beta-thalassemia gene. However, there has been no routine screening for thalassemia gene carriers. Several recognized methods of thalassemia screening are available. One of them is screening of prospective brides using several hematology parameters such as Mentzer index and red blood cells fragility; both are relatively straightforward and inexpensive compared to hemoglobin analysis or genetic testing. This study aimed to determine the frequency of beta-thalassemia minor suspects among students in the Medical Faculty of Mulawarman University. This study was a descriptive quantitative study with cross sectional approach that involved 160 participants. Participant's blood sample was collected for complete blood count and one tube osmotic fragility test (OTOFT). Mentzer index is calculated by dividing MCV values ​​with erythrocyte count. Participants were determined as beta-thalassemia minor suspects if they met following criterias: (1) MCV < 80 fL; (2) Mentzer index < 13; and (3) positive OTOFT result. This study demonstrated that 1.25% (n=2) of 160 participants were beta-thalassemia minor suspect. Further examination of hemoglobin electrophoresis or genetic testing is needed to further confirm this finding.